Orbit Design Elements of Chang’e 5 Mission - Zhong-Sheng Wang (American Association for the Advancement of Science (AAAS), 2021)
The three key orbit design technologies employed in the Chang’e 5 mission are identified and discussed in this paper: orbit design for lunar orbit rendezvous and docking, orbit design for precision lunar landing and inclination optimization, and orbit design for Moon-to-Earth transfer. First, an overview of the Chang’e 5 mission profile is presented, which is followed by detailed discussions of the three key orbit design technologies, including an introduction of the tracking-based orbit design methodology. Flight data are provided to demonstrate the correctness of the designs.